2016
DOI: 10.5899/2016/dea-00120
|View full text |Cite
|
Sign up to set email alerts
|

Computing Efficiency for Decision Making Units with Negative and Interval Data

Abstract: Data Envelopment Analysis (DEA) is a nonparametric method for identifying sources and estimating the mount of inefficiencies contained in inputs and outputs produced by Decision Making Units (DMUs). DEA requires that the data for all inputs and outputs should be known exactly, but under many qualifications, exact data are inadequate to model real-life situations. So these data may have different structures such as bounded data, interval data, and fuzzy data. Moreover, the main assumption in all DEA is that inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…About Adjusted DEA, it is a type of DEA for which interesting improvements were envisaged, such as the use of qualitative variables (Sherman & Zhu, 2006) and negative or an interval data (Piri et al, 2016). Thus, Adjusted DEA is appropriate for composite index elaboration, as it deals with data of various types and gives optimal weights for indicators.…”
Section: Discussionmentioning
confidence: 99%
“…About Adjusted DEA, it is a type of DEA for which interesting improvements were envisaged, such as the use of qualitative variables (Sherman & Zhu, 2006) and negative or an interval data (Piri et al, 2016). Thus, Adjusted DEA is appropriate for composite index elaboration, as it deals with data of various types and gives optimal weights for indicators.…”
Section: Discussionmentioning
confidence: 99%
“…During the same year, the probability in the DEA program was introduced under the name of Chance-constrained DEA Model (Land et al, 1993) Sherman and Zhu (2006). Since 2007, methods to treat negative and interval data in the DEA are conceived (Piri et al, 2016). In 2012, Lee and Zhu conceive an alternative method to traditional Super-Efficiency Model for ranking efficient units and removing outliers.…”
Section: Deamentioning
confidence: 99%
“…Emrouznejad and Yang (2016) proposed a performance index based on efficient and anti-efficient frontiers in DEA models without explicit inputs (DEA-WEI) and developed the corresponding performance index in quadratic DEA-WEI models. Piri et al (2016) proposed a method to evaluate the efficiency scores of DMUs with interval data in which the lower and upper bounds of intervals can take both negative and positive values. Amirteimoori et al (2017) suggested an approach to integrate the optimistic and pessimistic perspectives to obtain the interval efficiency scores of units with interval data.…”
Section: Introductionmentioning
confidence: 99%